Carbonation of hardened cement pastes: Influence of temperature. (January 2019) - Drouet, Emeline; Poyet, Stéphane; Le Bescop, Patrick; Torrenti, Jean-Michel; Bourbon, Xavier
Abstract: The impact of temperature on carbonation was investigated in laboratory conditions using a device developed for this purpose. Two hardened cement pastes (CEM I and CEM V/A) were tested between 20 °C and 80 °C at different levels of relative humidity (RH). The carbonation rate of the CEM I increased with temperature, whereas that of CEM V/A reached a maximum at around 50 °C.